2022
DOI: 10.1186/s12891-022-05877-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of patellar resurfacing, no resurfacing and selective resurfacing in primary total knee replacement: systematic review and meta-analysis of interventional and observational evidence

Abstract: Background Patellar resurfacing is optional during total knee replacement (TKR). Some surgeons always resurface the patella, some never resurface, and others selectively resurface. Which resurfacing strategy provides optimal outcomes is unclear. We assessed the effectiveness of patellar resurfacing, no resurfacing, and selective resurfacing in primary TKR. Methods A systematic review and meta-analysis was performed. MEDLINE, Embase, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The inclusion of patellar resurfacing in total knee arthroplasty remains a topic of ongoing debate, and a standardised approach has not been universally recommended for total knee prostheses performed in cases of haemophilic arthropathy. 28,29 Recognising the limitations of current implant designs in adequately restoring the anterior femoral anatomy, 30 it is predictable to anticipate that haemophilic arthropathies will also receive their share of the personalised surgical approach in the future. 31 One of the most striking data we found in our study were that the intercondylar depth decreased in the haemophilic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of patellar resurfacing in total knee arthroplasty remains a topic of ongoing debate, and a standardised approach has not been universally recommended for total knee prostheses performed in cases of haemophilic arthropathy. 28,29 Recognising the limitations of current implant designs in adequately restoring the anterior femoral anatomy, 30 it is predictable to anticipate that haemophilic arthropathies will also receive their share of the personalised surgical approach in the future. 31 One of the most striking data we found in our study were that the intercondylar depth decreased in the haemophilic group.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of patellar resurfacing in total knee arthroplasty remains a topic of ongoing debate, and a standardised approach has not been universally recommended for total knee prostheses performed in cases of haemophilic arthropathy 28,29 . Recognising the limitations of current implant designs in adequately restoring the anterior femoral anatomy, 30 even in knees affected by gonarthrosis, and considering the alterations in patellar size, tilt and inclination observed in haemophilic knees, along with the standard trochlear sulcus in knee prostheses, patellar resurfacing should be kept in mind in order to achieve more predictable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT of patients who did not undergo patellar resurfacing, patellar rim denervation using electrocautery did not appear to provide clinically relevant benefits with regard to anterior knee pain compared with no denervation 44 . With regard to patellar resurfacing, a systematic review and meta-analysis of RCTs revealed that resurfacing reduced anterior knee pain and revision risk compared with no resurfacing 45 . A prospective study showed that 75% of patients reported thigh pain on postoperative day 1 regardless of tourniquet or intramedullary guide use during the surgical procedure, but, at 2 weeks postoperatively, tourniquet use appeared to increase the odds of a quadriceps strain 46 .…”
Section: Surgical Techniquementioning
confidence: 99%
“…High-quality randomized-controlled trials involving selective resurfacing, the most common strategy in the United Kingdom and other countries, are needed based on the fact that limited observational data suggest that selective resurfacing may not be effective over other strategies. [5] In a study, the degree of intraoperatively identified patellar cartilage loss did not affect the short-term outcomes following primary TKR without patellar resurfacing. [6] Clinical and radiographic outcomes were not significantly different between the two groups according to intraoperatively graded cartilage lesions based on the International Cartilage Repair Society (ICRS) system: Group 1, Grades 0-2 (n=110); Group 2, Grades 3-4 (n=102).…”
mentioning
confidence: 94%
“…High-quality randomized-controlled trials involving selective resurfacing, the most common strategy in the United Kingdom and other countries, are needed based on the fact that limited observational data suggest that selective resurfacing may not be effective over other strategies. [ 5 ]…”
mentioning
confidence: 99%